Biochemical, Microbiological, and Sensory Properties of Dried Silver Carp (Hypophthalmichthys molitrix) Influenced by Various Drying Methods - Md. Golam Rasul; Bhaskar Chandra Majumdar; Faria Afrin; Mohammad Abu Jafor Bapary; A.K.M. Azad Shah (Fishes, 2018)
An experiment was performed to evaluate the effects of different drying methods with different pre-treatments on the physico-chemical, microbiological, and sensory properties of the silver carp, Hypophthalmichthys molitrix. In order to achieve this objective, the collected fresh fish were dried using traditional (without any pre-treatment), improved (fish soaked in a 5% salt solution for 10 min and then treated with chili powder (0.3%) and turmeric powder (0.3%)), and solar tunnel (fish soaked in a 5% salt solution for 10 min) drying methods. The results showed that the dried fish produced by the solar tunnel drying method were rehydrated more rapidly than the products produced by the traditional and improved drying methods. The moisture content of the dried H. molitrix was varied from 18.24 to 25.43% on a fresh matter basis. There was no significant (p > 0.05) difference found regarding the protein, lipid, and ash content among the different drying methods on a dry matter basis. The total volatile base nitrogen (TVB-N) contents ranged between 37.58 and 45.03 mg/100 g, and significantly (p < 0.05) the lowest TVB-N was observed in dried fish produced by the solar tunnel drying method. Moreover, the highest peroxide and acid values were found in the traditionally produced dried fish as compared with the fish dried by the improved and solar tunnel drying methods. The aerobic plate count of dried fish ranged from 4.52 to 7.51 log CFU/g. The sensory evaluation results revealed that the solar-dried products showed superior quality than the products produced by the traditional and improved drying methods. The results revealed that the dried fish produced by the solar tunnel drying method provided the best product in terms of physico-chemical, microbiological, and sensory aspects.